Robust weak antilocalization due to spin-orbital entanglement in Dirac material Sr3SnO - H. Nakamura (Nature Portfolio, 2020)
The spin texture in presence of both inversion and time-reversal symmetries has been difficult to observe. Here, Nakamura et al. report evidence of hidden entanglement between spin and momentum in antiperovskite Dirac material Sr3SnO.